EFFICIENT VALIDATION OF RFID COMPLEX EVENTS CONSIDERING BUSINESS PROCESS STRUCTURE - Zhang, Shuzhu; Bae, Hyerim; Koo, Hoonyoung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
In parallel with the recent development of enterprise information systems, business processes have become more complicated. Notably, increasing number of techniques and tools, including radio frequency identification (RFID), are being employed in daily operations, exerting a growing influence on business process execution and performance. According to an analysis of logistics processes in which RFID devices are used, the RFID event is an essential element, integral to the understanding of when and how the logistics flow proceeds. In this paper, focusing on complex events as opposed to basic events, we provide an efficient semantic validation mechanism for complex events in reference to the structures of business processes. Referring to our complex event patterns, readers can design their own event formats to enrich the complex event repository. In order to control business processes, we need to consider two issues. First, in reference to business process structure, we provide semantic rules for efficient validation of complex events. Second, in the validation mechanism, we introduce two decomposition approaches to improve the correctly formatted complex events, which play a significant role. Finally, we validated our approach through the experiments